MoO3-P material, preparation method and ammonium storage material

By phosphating treatment and immersion treatment on MoO3, the MoO3-P material was formed, which solved the problems of low MoO3 electrode capacity and poor ion transport performance, and significantly improved the reaction kinetics and cyclic stability of the electrode.

CN119650308APending Publication Date: 2025-03-18CHINA THREE GORGES UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411656969.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

When MoO3 is an aqueous ammonium ion battery electrode, it has low capacity, poor conductivity and ion transmission performance, which affects the electrode's fast charging and discharge capability.

Method used

MoO3 was prepared on a carbon cloth substrate by hydrothermal method, and then P-O bond was introduced by phosphating treatment to form MoO3-P. Subsequently, MoO3-P is immersed in ammonium sulfate solution for immersion treatment, and sulfate ions are adsorbed on the electrode surface by magnetic stirring, preventing NH4+ hydrolysis, and inducing H+ and NH4+ to co-embed MoO3, improving the capacity and cyclic stability of the electrode material.

Benefits of technology

After phosphating, part of Mo6+ is converted into Mo5+, creating a large number of O vacancy, reducing the internal resistance and charge transfer resistance of the electrode, and improving the reaction kinetics and capacity; after immersion of ammonium sulfate, the electrode surface adsorbs sulfate ions, preventing hydrolysis, and improving the cyclic stability of the electrode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650308A_ABST
    Figure CN119650308A_ABST
Patent Text Reader

Abstract

The invention discloses a method for improving ammonium storage performance of MoO3 through surface engineering. The preparation method comprises the following steps: firstly, growing MoO3 on a carbon cloth substrate by adopting a hydrothermal method; then phosphating the MoO3 to obtain MoO3-P, introducing a P-O bond, and enabling the MoO3 to generate a large number of O vacancies at the same time; and further soaking the MoO3-P in an ammonium sulfate solution to obtain a final product. In a three-electrode electrochemical system formed by the ammonium sulfate electrolyte, the electrochemical performance evaluation on the obtained sample shows that the specific capacity of the sample is up to 260.7 mAh g <-1 > under the current density of 10 mA cm <-2 >, and the capacity value is kept at 98.87% after 2100 charge-discharge cycles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of aqueous ammonium ion hybrid supercapacitors, and specifically relates to a method for improving the ammonium storage performance of MoO3 by surface engineering, and aims to improve the ammonium ion storage capacity and cycle stability of MoO3. Background Art

[0002] With the rapid development of modern society, the overexploitation and use of fossil energy has caused a series of environmental problems such as resource scarcity, greenhouse effect and air pollution. The development of eco-friendly renewable energy is urgent. However, the intermittent nature of clean energy such as solar energy and wind energy, as well as the disadvantage of being unable to provide energy continuously, means that they can only be used in specific areas. The development of efficient energy storage equipment is an effective way to solve this problem. Supercapacitors have attracted widespread attention in recent years due to their advantages such as fast charge and discharge rates, good cycle stability, and high power capacity.

[0003] Aqueous supercapacitors can not only achieve high power density and high energy density, but also have the advantages of high safety, low cost and environmental protection. + , K + , Zn 2+ ,Mg 2+ , Ca 2+ , Al 3+ etc.) and non-metallic cations (such as H + 、H3O + NH4 + ) is considered as an alternative carrier in aqueous supercapacitors. However, due to the cost and limited metal resource reserves of metal cations, the study of non-metallic cations as charge carriers in aqueous energy storage systems is particularly important. Among them, non-metallic cations NH4 + It is considered an emerging charge carrier and is widely used in energy storage systems for research and commercial applications. + Not only does it show a lighter molar mass (18 g / mol), but also the hydrated ion radius is smaller (3.3 Å), which is more conducive to the diffusion of ions in the solution and promotes the transmission to the internal structure of the material without obvious structural distortion, which is more conducive to improving the power density of the device. + Charge transfer can be carried out between the electrodes through the formation / breakage of hydrogen bonds, thereby obtaining a higher energy storage capacity than metal ions and having an advantage in energy density. + The development of memory devices has attracted much attention.

[0004] The researchers compared the electrochemical properties of different crystalline MoO3 and found that NH4 +The reversible process of hydrogen bond formation / breaking between MoO3 and O atoms. When MoO3 is used as an electrode material, the Mo atom changes from +6 to +4 and +5 during the charge and discharge process. Although MoO3 has the advantages of low cost, diverse valence states, and eco-friendliness, the main problems faced when used as an electrode for aqueous ammonium ion batteries are: (1) It is restricted by a single NH4 + Insertion / extraction mechanism, the capacity of the electrode material is low (usually less than 200 mAh g −1 ); (2) Due to the low electrical conductivity and ion transport, the reaction kinetics of the electrode material are poor, which affects the electrode's ability to quickly charge and discharge. Summary of the invention

[0005] The purpose of the present invention is to solve the problems of low actual capacity, unsatisfactory conductivity and ion transmission performance of MoO3, and to propose a method for improving the ammonium storage performance of MoO3 by surface engineering. Firstly, MoO3 is prepared on a carbon cloth substrate by a hydrothermal method, and then PO bonds are introduced by phosphating treatment to obtain MoO3-P. After the MoO3-P is immersed in an ammonium sulfate solution, the final product can be obtained.

[0006] The invention provides a MoO3-P material, wherein P in the MoO3-P material is doped into the MoO3 structure so that the XRD of the material has characteristic peaks at about 12.8°, about 25.7°, about 27.3° and about 40°.

[0007] In the MoO3-P material, P is doped into MoO3 to achieve Mo 6+ Partially converted to Mo 5+ ; The morphology of the MoO3-P material is curved nanowire-like.

[0008] The present invention provides a method for preparing a MoO3-P material, comprising the following steps: (1) Prepare the acidified solution: add sodium molybdate dihydrate and concentrated hydrochloric acid to deionized water in sequence and stir until fully dissolved; (2) Substrate cleaning and acidification: The carbon cloth was ultrasonically cleaned in anhydrous ethanol and deionized water in turn. After drying, it was immersed in an acid solution at 25-30 °C for 20 min. After being taken out, it was dried in an oven and then annealed in a CVD tube furnace. (3) Preparation of MoO3 precursor: ammonium molybdate and concentrated nitric acid are added to deionized water in sequence, stirred until completely dissolved, and then transferred to the inner lining of a reactor, and the acidified carbon cloth is placed in the reactor, and the reactor is sealed, and a MoO3 precursor is obtained by hydrothermal reaction; (4) Phosphating treatment: The sample obtained in step (3) and sodium metaphosphate are placed in a CVD tube furnace, with the sodium metaphosphate placed upstream of the gas source and the MoO3 precursor placed downstream of the gas source. The samples are then annealed in the tube furnace under argon conditions to obtain MoO3-P.

[0009] (5) Ammonium sulfate soaking treatment: The sample obtained in step (4) is placed in an ammonium sulfate solution and subjected to magnetic stirring for a period of time to obtain the final product.

[0010] (6) Three-electrode system setup: The sample obtained in step (5) was used as the working electrode, the platinum sheet was used as the counter electrode, the saturated calomel electrode was used as the reference electrode, and the ammonium sulfate solution was used as the electrolyte. The electrochemical performance was tested using an electrochemical workstation three-electrode system.

[0011] In the step (1), the molar ratio of sodium molybdate dihydrate to hydrochloric acid is 1:10-15. In the step (2), the temperature is raised to 300-350°C at a rate of 5-10°C / min during the annealing process, and then lowered to room temperature after annealing for 5-10 minutes. During the heating, annealing and cooling processes, the argon gas flow rate is 20-30 sccm.

[0012] In the step (3), the molar ratio of ammonium molybdate to nitric acid is 1:100-120, the hydrothermal reaction temperature is 160-180° C., and the heating time is 6-8 hours.

[0013] In the step (4), the temperature is raised to 200-300°C at a rate of 5-10°C / min during the annealing process, and then lowered to room temperature after annealing for 1-2 hours. During the heating, annealing and cooling processes, the argon gas flow rate is 20-30sccm.

[0014] The present invention also provides an ammonium storage electrode, comprising a MoO3-P material prepared by the method described in any one of claims 3 to 6, wherein the MoO3-P material or the MoO3-P material prepared by the method is subjected to magnetic stirring treatment in an ammonium sulfate solution for a period of time to obtain a final product.

[0015] Another object of the present invention is to provide an ammonium ion supercapacitor, comprising the use of the ammonium storage electrode as a working electrode, a platinum sheet as a counter electrode, a saturated calomel electrode as a reference electrode, and an ammonium sulfate solution as an electrolyte. The ammonium sulfate concentration is 0.5M~2M.

[0016] The technical solution of the present invention is to grow MoO3 nanometers on the surface of carbon cloth by hydrothermal method; to generate PO bonds on the surface of MoO3 by phosphating treatment, and to generate a large number of O vacancies, thereby improving the transmission and transfer rate of electrons in the material; to soak in ammonium sulfate, combined with magnetic stirring, to make the electrode surface adsorb a large number of sulfate ions, thereby preventing NH4 +During the hydrolysis on the electrode material surface and the induction of charge and discharge process, H + With NH4 + Co-embedding MoO3 can improve the capacity of the electrode material; selecting a suitable three-electrode system can improve the cycle stability of MoO3.

[0017] The beneficial effects of the present invention are as follows: (1) After phosphating, part of Mo 6+ Transformed into Mo 5+ , and a large number of O vacancies are generated, which significantly reduces the internal resistance and charge transfer resistance of the electrode, thereby improving the reaction kinetics of the electrode; (2) After phosphating, PO bonds are formed on the surface of MoO3, which accelerates the diffusion and adsorption of ammonium ions and improves the capacity and rate performance of the electrode material; (3) After phosphating, the crystallinity of MoO3 is reduced, and the ion transmission channel is more open and continuous, which can greatly reduce the obstruction of ions in the transmission process, thereby improving the electrochemical activity; (4) After ammonium sulfate immersion, a large number of sulfate ions are adsorbed on the surface, which effectively prevents NH4 + Hydrolysis on the electrode surface prevents the hydrolysis product NH3 H2O from corroding MoO3, and at the same time induces H + With NH4 + co-embedded in MoO3 to increase the capacity of the electrode material; (5) Select a suitable three-electrode system to ensure that H + With NH4 + It can be repeatedly embedded / de-embedded in MoO3 in a continuous and stable manner, ensuring the cycle stability of the electrode material.

[0018] The technical method of the present invention comprises the following steps: (1) Prepare the acidified solution: add sodium molybdate dihydrate and concentrated hydrochloric acid to deionized water in sequence and stir until fully dissolved; (2) Substrate cleaning and acidification: The carbon cloth was ultrasonically cleaned in anhydrous ethanol and deionized water in turn. After drying, it was immersed in an acid solution at 25-30 °C for 20 min. After being taken out, it was dried in an oven and then annealed in a CVD tube furnace. (3) Preparation of MoO3 precursor: ammonium molybdate and concentrated nitric acid are added to deionized water in sequence, stirred until completely dissolved, and then transferred to the inner lining of a reactor, and the acidified carbon cloth is placed in the reactor, and the reactor is sealed, and a MoO3 precursor is obtained by hydrothermal reaction; (4) Phosphating treatment: The sample obtained in step (3) and sodium metaphosphate are placed in a CVD tube furnace, with the sodium metaphosphate placed upstream of the gas source and the MoO3 precursor placed downstream of the gas source. The samples are then annealed in the tube furnace under argon conditions to obtain MoO3-P.

[0019] (5) Ammonium sulfate soaking treatment: The sample obtained in step (4) is placed in an ammonium sulfate solution and subjected to magnetic stirring for a period of time to obtain the final product.

[0020] (6) Three-electrode system setup: The sample obtained in step (5) was used as the working electrode, the platinum sheet was used as the counter electrode, the saturated calomel electrode was used as the reference electrode, and the ammonium sulfate solution was used as the electrolyte. The electrochemical performance was tested using an electrochemical workstation three-electrode system.

[0021] The technical solution of the present invention applies the electrode obtained above to an ammonium ion supercapacitor. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Attached Figure 1 This is the XRD of the product obtained after steps (1) to (4) in Example 1 and steps (1) to (3) in Example 2.

[0023] Attached Figure 2 a, 2b are SEM images of the MoO3 electrode obtained in Example 2 under different magnifications; 2c, 2d are SEM images of the MoO3-P electrode obtained in Example 1 under different magnifications.

[0024] Attached Figure 3 a is Example 1 (sample MoO3-P 0.50 ), Example 2 (Sample MoO3), Example 3 (Sample MoO3-P 0.25 ), Example 4 (Sample MoO3-P 0.75 ), Example 5 (Sample MoO3-P 1.00 ) at 10 mV s -1 CV curve comparison under scanning rate; Figure 3 b is a comparative diagram of the GCD curves of Example 1, Example 2, Example 3, Example 4, and Example 5; Figure 3 c is a comparison diagram of the EIS curves of Example 1, Example 2, Example 3, Example 4, and Example 5.

[0025] Attached Figure 4 a, 4b, 4c are the SEM results of Example 6, Figure 4 d, 4e, and 4f are SEM results of the examples.

[0026] Attached Figure 5 a is the SEM picture of Example 6 after 50 cycles, Figure 5 b is the SEM result of Example 6 after 200 cycles, Figure 5 c is the SEM picture of Example 1 after 50 cycles, Figure 5 d is the SEM result of Example 1 after 200 cycles.

[0027] Attached Figure 6 a, 6b, 6c are the ex-situ XPS results of Mo 3d, N 1s and O 1s during the charge and discharge process of Example 1. Figure 6 d, 6e, and 6f are the ex-situ XPS results of Mo 3d, N 1s, and O 1s during the charge and discharge process of Example 3.

[0028] Attached Figure 7 The figures are comparative drawings of the electrochemical performance of Example 1 and Example 7. a is a cycle stability graph, b is a CV curve graph, c is a GCD curve graph, and d is an EIS graph. DETAILED DESCRIPTION

[0029] In order to further understand the content and features of the present invention, embodiments of the present invention are given below. It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.

[0030] The experimental methods in the following examples are conventional methods unless otherwise specified.

[0031] Example 1 Step (1): Add 2.5 g of sodium molybdate dihydrate and 5 ml of concentrated hydrochloric acid to deionized water in sequence and stir until fully dissolved.

[0032] Step (2): After ultrasonically cleaning and drying a carbon cloth with an area of ​​2 cm × 4 cm with anhydrous ethanol and deionized water, the cleaned carbon cloth is immersed in an acid solution at 25-30°C for 20 minutes, taken out and dried with a hair dryer, and then annealed in a CVD tube furnace. The molar concentration of concentrated hydrochloric acid is 37 wt.%; during the annealing process, the temperature is raised to 340°C at a rate of 10°C / min, and then cooled to room temperature after annealing for 5 minutes. During the heating, annealing and cooling process, the argon gas flow rate is 20-30 sccm.

[0033] Step (3): 1.06 g of ammonium molybdate and 6 ml of concentrated nitric acid are added to deionized water in sequence, stirred until fully dissolved, and then poured into the reactor liner, and then the acidified carbon cloth is placed in the liner, sealed with a stainless steel jacket, heated at 180°C for 8 hours, and then taken out, ultrasonically cleaned in deionized water and anhydrous ethanol, respectively, and dried in an oven to obtain a MoO3 precursor. The molar concentration of the concentrated nitric acid is 65 wt.%.

[0034] Step (4): Phosphate the precursor. Place the precursor and 500 mg of sodium metaphosphate in a CVD tube furnace, with sodium metaphosphate placed upstream of the gas source and MoO3 precursor placed downstream of the gas source. Anneal in the tube furnace under argon to obtain phosphorus-modified molybdenum oxide. Heat to 300°C at a rate of 5°C / min, anneal for 90 minutes, and then cool to room temperature. During the heating, annealing and cooling process, the argon flow rate is 20-30 sccm. The obtained sample is recorded as MoO3-P 0.50g .

[0035] Step (5): At room temperature, MoO3-P 0.50g Immerse in 1 M ammonium sulfate solution and stir magnetically for 120 min.

[0036] Step (6): The sample obtained in step (5) is used as a working electrode, a platinum sheet is used as a counter electrode, a saturated calomel electrode is used as a reference electrode, and a 1M (NH4)2SO4 solution is used as an electrolyte. The electrochemical performance is tested using an electrochemical workstation three-electrode system.

[0037] Example 2 Compared with Example 1, step (4) is not performed, and the rest is the same as Example 1.

[0038] Example 3 Compared with Example 1, in step (4), the amount of sodium metaphosphate is 0.25 g, and the rest is the same as in Example 1. The obtained sample is recorded as MoO3-P 0.25g .

[0039] Example 4 Compared with Example 1, in step (4), the amount of sodium metaphosphate is 0.75 g, and the rest is the same as in Example 1. The obtained sample is recorded as MoO3-P 0.75g .

[0040] Example 5 Compared with Example 1, in step (4), the amount of sodium metaphosphate is 1.00 g, and the rest is the same as in Example 1. The obtained sample is recorded as MoO3-P 1.00g .

[0041] Example 6 Compared with Example 1, the ammonium sulfate solution in step (5) is changed to 2M ammonium acetate solution, and the electrolyte in step (6) is 2M ammonium acetate. The rest is the same as Example 1.

[0042] Example 7 Compared with Example 1, the electrolyte in step (7) is 2M ammonium acetate, and the rest is the same as Example 1.

[0043] In order to illustrate the effect of phosphating treatment, Figure 1a, 1d compare the XRD patterns of the products obtained after steps (1)-(4) of Example 1 and steps (1)-(3) of Example 2. Both products are MoO3 (PDF#00-035-0609), but the characteristic peaks of the product in Example 1 show different degrees of broadening and intensity reduction compared with those in Example 2. This indicates that the crystallinity of the product after phosphating annealing treatment is significantly reduced, and the ion transmission channel is more open and continuous, which can greatly reduce the obstruction of ion transmission, thereby improving the electrochemical activity. Figure 2 The microscopic morphology of the products obtained in Example 1 and Example 2 are both nanowire structures. The nanowires in Example 1 show obvious bending, which may be caused by the release of water and hydroxyl groups during the phosphating process. In addition, when P is doped into the sample during the phosphating process, it promotes the Mo 6+ Partially converted to Mo 5+ (Attached Figure 6 a, 6d), which creates O vacancies in the sample and thus improves the electrochemical activity of the sample.

[0044] By Example 1 (Sample MoO3-P 0.50 ), Example 2 (Sample MoO3), Example 3 (Sample MoO3-P 0.25 ), Example 4 (Sample MoO3-P 0.75 ), Example 5 (Sample MoO3-P 1.00 The comparison of electrochemical performance of ) further illustrates the importance of proper phosphating. Figure 3 As shown in the figure, after phosphating, the CV curve of the sample (attached Figure 3 a) shows different degrees of increase, GCD curve (attached Figure 3 b) The discharge time showed different degrees of increase, indicating that the phosphating treatment has a significant effect on improving the capacity of MoO3, among which the MoO3-P obtained in Example 1 0.50 The specific capacity is the largest at a current density of 10 mA cm -2 The specific capacity reaches 260.74 mAh g -1 , while the specific capacitance of MoO3 obtained in Example 2 is only 112.97 mAh g -1 Attached Figure 3 c shows the electrochemical impedance spectroscopy (EIS) curves of Example 1, Example 2, Example 3, Example 4, and Example 5, and the charge transfer resistance (R ct, semicircle diameter) are significantly smaller than those of MoO3, indicating that after phosphating annealing, the transmission resistance of electrons inside the electrode material and between the electrode and the electrolyte interface is reduced. This is because phosphating produces O vacancies in the crystal, increasing the reactive sites and improving the electrochemical reaction activity of the material. In addition, the slope in the low-frequency region varies with the amount of phosphating. MoO3-P 0.50g The slope is the largest, indicating that the low-frequency region exhibits more obvious diffusion characteristics, which improves the ion transport kinetics and leads to higher charge storage capacity.

[0045] To illustrate the effect of surface adsorption of sulfate ions, Figure 4 The SEM results of Example 1 and Example 6 are given. It can be seen that after immersing in NH4CH3COOH solution for 2 hours, a large number of holes appear on the surface of the nanowires. This is due to the NH4 + After hydrolysis, NH3 H2O is produced, which reacts with MoO3, causing MoO3 corrosion, and it is difficult to observe the initial MoO3-P nanowire nanomorphology. After immersing in (NH4)2SO4 solution for 2 hours, the surface of the nanowires is still intact and no corrosion occurs. This is due to the large amount of SO4 adsorbed on the surface. 2- Ions prevent NH4 + Hydrolysis of MoO3 is avoided. Figure 5 The SEM images of Example 1 and Example 6 after 50 and 200 cycles of charge and discharge show that the corrosion of the electrode material becomes more and more serious in the NH4CH3COOH electrolyte. However, in the (NH4)2SO4 electrolyte, no corrosion phenomenon occurs with the increase of the number of charge and discharge cycles, which again shows that the SO4 adsorbed on the surface 2- Protective effect of ions on MoO3.

[0046] In order to illustrate the surface adsorption of SO4 2- Ion-induced NH4 + / H + In order to investigate the effect of co-embedding, the ex-situ XPS characterization of the charge and discharge process was performed on Example 1 and Example 3, respectively. Figure 6 As shown in b, when Example 1 is discharged, NH4 + It will be embedded in the electrode material to form hydrogen bonds with the electrode material. The -N+H- peak in the N 1s spectrum will be enhanced. During charging, NH4 + From the electrode material, back to the electrolyte, at this time, -N+H- peak weakened, reflecting the NH4 + Reversible insertion and extraction. In the process of discharge-charge-discharge, the area ratio of the -NH- fitting peak changes from 16.15% to 4.9% to 16.17%. This change trend reflects the NH4 +Reversible embedding and extraction. In the XPS results of Example 3 (Attached Figure 6 e), during the discharge-charge-discharge process, the area of ​​the -NH- fitting peak changes from 7.1% to 4.6% to 8.3%, showing the same trend as in Example 1, indicating that NH4 also exists during the charge-discharge process + However, during discharge, the area of ​​the -NH- fitting peak is significantly lower than that of Example 1, which means that NH4 + The embedding amount is much smaller than that in Example 1, which indicates that the immersion in ammonium sulfate solution in step (5) of Example (1) is one of the keys to improving the capacity.

[0047] As attached Figure 6 As shown in c, during charging, the intensity of Mo-O in the O 1s spectrum of Example 1 increases, while the intensity of Mo-OH decreases. During discharge, the intensity of Mo-O decreases while the intensity of Mo-OH increases, indicating that in addition to NH4 + Embedded in the MoO3 lattice, H + ions are also embedded in the lattice; during the charging process, the previously embedded H + The ions are extracted from the electrode material and returned to the electrolyte, causing some Mo-OH bonds to break and Mo-O bonds to reform. This shows that during the discharge-charge-discharge process, H + Can be with NH4 + The XPS results in Example 3 (see Appendix) show that the capacity of the MoO3 can be reversibly embedded / deintercalated together, thereby further improving the capacity. Figure 6 f), during the discharge stage, the relative intensity of Mo-OH decreases, while the relative intensity of Mo-O increases. During the charge stage, the relative intensity of Mo-OH increases, while the relative intensity of Mo-O decreases, which is completely opposite to the rule in Example 1. The above results show that the surface adsorption of SO4 2- To induce NH4 + / H + The necessity of co-embedding.

[0048] In order to illustrate the necessity of selecting a suitable electrolyte, the electrochemical performance of Example 1 and Example 7 is compared. Figure 7 Attached Figure 7 b, 7c show that the initial capacity of the samples in ammonium sulfate electrolyte and ammonium acetate electrolyte is similar. However, in ammonium acetate electrolyte, the capacity decays rapidly to 58.52% of the initial value after only 250 cycles. In contrast, in ammonium sulfate electrolyte, the capacity retention rate is still as high as 98.87% after 2100 cycles. Figure 7 d is the electrochemical impedance spectroscopy (EIS) curve of the two electrolytes. The equivalent circuit consists of the equivalent series resistance R s , Charge transfer resistance R ct, Warburg resistance Z w , double layer capacitance C EDLC , and faradic pseudo capacitor C f Composition. R of MoO3-P-AC s is 4.22Ω and R ct is 0.30Ω, while the R s is 3.52Ω and R ct It is 0.24Ω, which means that the electron transmission and transfer process are faster in the ammonium sulfate electrolyte.

Claims

1. A MoO3-P material, characterized in that: The P in the MoO3-P material is doped into the MoO3 structure, so that the XRD of the material has characteristic peaks at about 12.8°, about 25.7°, about 27.3° and about 40°.

2. The MoO3-P material according to claim 1, characterized in that In the MoO3-P material, P is doped into MoO3 to achieve Mo 6+ Partially converted to Mo 5+ ; The morphology of the MoO3-P material is curved nanowire-like.

3. A method for preparing the MoO3-P material according to claim 1 or 2, characterized in that: The steps include: (1) Prepare the acidified solution: add sodium molybdate dihydrate and concentrated hydrochloric acid to deionized water in sequence and stir until fully dissolved; (2) Substrate cleaning and acidification: The carbon cloth was ultrasonically cleaned in anhydrous ethanol and deionized water in turn. After drying, it was immersed in an acid solution at 25-30 °C for 20 min. After being taken out, it was dried in an oven and then annealed in a CVD tube furnace. (3) Preparation of MoO3 precursor: ammonium molybdate and concentrated nitric acid are added to deionized water in sequence, stirred until completely dissolved, and then transferred to the inner lining of a reactor, and the acidified carbon cloth is placed in the reactor, and the reactor is sealed, and a MoO3 precursor is obtained by hydrothermal reaction; (4) Phosphating treatment: The sample obtained in step (3) and sodium metaphosphate are placed in a CVD tube furnace, with the sodium metaphosphate placed upstream of the gas source and the MoO3 precursor placed downstream of the gas source. The MoO3-P is annealed in the tube furnace under argon conditions to obtain MoO3-P.

4. The method for preparing MoO3-P material according to claim 3, characterized in that: In step (1), the molar ratio of sodium molybdate dihydrate to hydrochloric acid is 1:10-15; in step (2), the temperature is raised to 300-350°C at a rate of 5-10°C / min during annealing, and then cooled to room temperature after annealing for 5-10 minutes. The argon flow rate during annealing is 20-30sccm.

5. The method for preparing MoO3-P material according to claim 1, characterized in that: In the step (3), the molar ratio of ammonium molybdate to nitric acid is 1:100-120, the hydrothermal reaction temperature is 160-180° C., and the heating time is 6-8 hours.

6. The method for preparing MoO3-P material according to claim 1, characterized in that: In step (4), the temperature is raised to 200-300°C at a rate of 5-10°C / min during the annealing process, and then lowered to room temperature after annealing for 1-2 hours. The argon gas flow rate during the annealing process is 20-30sccm.

7. An ammonium storage electrode, characterized in that The invention comprises a MoO3-P material prepared by the method described in any one of claims 3 to 6.

8. The ammonium storage electrode according to claim 7, characterized in that: The MoO3-P material according to claim 1 or 2 or the MoO3-P material prepared by the method according to any one of claims 3 to 6 is subjected to magnetic stirring for a period of time to obtain the final product.

9. The ammonium storage electrode according to claim 8, characterized in that: The concentration of ammonium sulfate is 0.25~2M, and the stirring time is 60min~240min.

10. An ammonium ion supercapacitor, characterized in that: The method comprises using the ammonium storage electrode described in any one of claims 7 to 9 as a working electrode, a platinum sheet as a counter electrode, a saturated calomel electrode as a reference electrode, and an ammonium sulfate solution as an electrolyte.